Dividend Policy pada Perusahaan Perbankan yang Terdaftar Di BEI - Zakaria Zakaria; Fajar Rina Sejati; Murti Muti (Kompartemen : Jurnal Ilmiah Akuntansi, 2020)
Dividend policy is a decision taken by a company related to dividends, whether profits will be distributed to shareholders or investors in the form of dividends or profits will be retained as retained earnings for investment financing in the future. Factors that can influence dividend policy include current ratio, debt to equity ratio, net profit margin, investment opportunity set. The population in this study are banking companies listed on the Indonesia Stock Exchange in the 2015-2018 period. The samples obtained are based on purposive sampling techniques and obtained by 9 companies. The data analysis technique used is multiple linear regression analysis. The analysis shows that the debt to equity ratio, investment opportunity set has a positive effect and net profit margin has a negative effect on the dividend policy. However, the current ratio has no effect on the dividend policy.